Treatment of patients with chronic pruritus of unknown origin with dupilumab. (3rd April 2022) - Jeon, Jiehyun; Wang, Fang; Badic, Asima; Kim, Brian S.
Abstract: Background: Chronic pruritus of unknown origin (CPUO) is a highly debilitating disease that lacks effective treatments. This study explores a new therapeutic strategy with dupilumab. Objectives: To examine whether patients with CPUO demonstrate clinical response to dupilumab. Patients and methods: This is a retrospective case series examining all patients with CPUO who were treated with dupilumab from March 2017 to December 2019 at a tertiary referral clinic at Washington University School of Medicine in St. Louis, MO. Numerical rating scale (NRS) itch score changes over time were recorded and analyzed. Results: Fifteen patients (67% women; mean [SD] age, 68.7 [12.6] years [range, 42–88 years]) were included in the analysis. All patients had a diagnosis of CPUO for a mean [SD] 2.6 [2.8] years. The median [IQR] pruritus NRS itch score before dupilumab injection was 8 [8–10] and the final median [IQR] NRS itch score was 1 [0–2.5]. The mean [SD] reduction in the NRS itch score was 7.0 [1.9]. Dupilumab was well tolerated with one report of mild injection site reaction that was self-resolving. Conclusion: This study suggests that dupilumab may be an effective treatment for patients with CPUO and supports the design of future randomized placebo-controlled trials to prove its efficacy.